Building a Spending Plan: All Six Steps - Nayda I. Torres; Josephine Turner; Brenda C. Williams (EDIS)
Follow the six steps in this series to learn how to calculate your expenses and determine your financial goals. With this information, you can compare your expenses against your income to find out how to best budget your money. Fill out these worksheets to build your own spending plan. This revised publication collects all six steps of the Building a Spending Plan series in one document. Written by Nayda I. Torres, Josephine Turner, and Brenda C. Williams, and published by the UF Department of Family, Youth and Community Sciences, July 2012.